(untitled) (Northern International Medical College Journal, 2018)
Background :_The spectrum of respiratory illness is wide and includes diseases of upper and lower airways, communicable and non-communicable types. The variation in pattern of morbidity mortality of respiratory illness may be affected by different environmental and climatic variation in different parts of the world. Objective : The present study intended to explore the pattern of respiratory illnesses seen in Bangladeshi children admitted with respiratory illnesses. Methods :_The present prospective observational study was conducted in children up to 12 years of age admitted with acute respiratory illness in pulmonology unit of Dhaka Shishu (Children) Hospitalfrom July 2012 to July 2013. All children between the age limit with acute respiratory illness were included in the study. A standardized questionnaire was formulated and pretested. Then the data were collected through interview by using the questionnaire. Data were analyzed using SPSS version 17. Results : Total 1169 patients were admitted under pulmonology unit during July 2012 to June 2013 among them 324(27.7%) were admitted with respiratory diseases. Among the respiratory diseases Pneumonia (71.2%), Acute Bronchiolitis (20.1%), Bronchial Asthma (4.2%) and TB (2.7%) were commonest. Bronchopneumonia, Acute Bronchiolitis, Bronchial Asthma and TB was common among under 5 children and less common after 5 years. Male were predominate in every cases. Majority of respiratory cases were belonged to poor socioeconomic status. Pneumonia (50.7%) and Acute Bronchiolitis (58.5%) cases were found during autumn and late autumn. Asthma was common during late autumn and winter and Tuberculosis was common throughout the year. Mortality was higher among pneumonia cases. Conclusions :_Respiratory illness contributes most common cause of admission in tertiary care pediatric hospital. Bronchopneumonia is still the commonest respiratory disease with leading cause of mortality. Northern International Medical College Journal Vol.9(2) Jan 2018: 308-310